Professional learning to support social and emotional skills in the preschool classroom: A randomized controlled trial of Sesame Street’s Building a Connected Community online course - Danielle Riser; Leanne Elliott; Tina Ryznar; Chanel Brown; David Cohen; Antonio Freitas; Katie Dahlke (Social and Emotional Learning: Research, Practice, and Policy)
Building social and emotional skills during early childhood is crucial, and preschool classrooms are an ideal context to support children’s social and emotional competence. This classroom-level randomized controlled trial examined the implementation and impact of Building a Connected Community, a digital course and set of resources created by Sesame Workshop to help preschool teachers support children’s social and emotional skills and engage families in the classroom. The sample included 70 preschool classrooms at 20 programs across the United States. Classrooms were randomly assigned to either receive Building a Connected Community or continue with business as usual (control). Eighty percent of teachers assigned to receive Building a Connected Community implemented it with fidelity. Teachers in the Building a Connected Community condition showed significantly higher self-efficacy and practices supporting children’s social and emotional competence compared to teachers in the control condition. They also had significantly higher caregiver engagement practices compared to teachers in the control condition. Children in the Building a Connected Community condition had significantly higher social and emotional competence compared to children in control classrooms based on teacher reporting in the postsurvey. The study also examined the impact on teachers’ self-efficacy in engaging with caregivers, caregiver reports of teachers’ engagement practices, caregivers’ relationships with teachers, and caregiver reports of children’s social and emotional competence but did not find a significant effect for these outcomes. Overall, the data suggest that Building a Connected Community is a promising and easily accessible intervention for supporting social and emotional skills in the preschool classroom.